INFLUENTIAL INDIVIDUALS ON SOCIAL NETWORKS: AN EXAMPLE OF FACEBOOK IN GEORGIA - Babutsidze, Zakaria; Lomitashvili, Tengiz; Turmanidze, Koba (European Scientific Journal, ESJ, 2014)
The paper analyzes a unique dataset with information on the demographic characteristics and behavior of Georgian users of Facebook. Based on this representative data, we construct a network of 2589 Facebook users and 4473 connections among them. The data also include the behavior of a subset of the respondents with respect to the opportunity to exert influence over their social contacts. We study the data using tools of Social Network Analysis. The major aim is to characterize the identity of influential individuals on Georgian Facebook. The main conclusion is that young women occupy key positions in the network and possess disproportionately high structural power, which provides them unique opportunity to influence others’ behavior and control the flow of information from various parts of the network.